Trendscouts und Trendsetter im digitalen Zeitalter : IT-Journalisten: Wer sie sind, wie sie arbeiten, was sie denken. - Jackob, Nikolaus (Media Convergence / Medienkonvergenz., 2013)
Computer technologies continue to develop at breakneck speed, with a rapid flow of new innovations to the market. The survey of journalists undertaken in this work addresses four key questions: How do IT journalists view their professional role? How do they assess their impact on consumers and manufacturers? What sort of ties do they have to industry and the public? How will information technology change our society in the future?